Granular Cell Tumor in the Brain of a Dog - Maglaty, Marisa; Woolard, Kevin D. (Brazilian Journal of Veterinary Pathology, 2021)
10 year-old, female spayed, Golden Retriever/Poodle mix. This patient had a mass removed laparoscopically from the right adrenal gland (cortical adenoma) and was started on a low dose of prednisone post-operatively. Eight days postop, she began having cluster seizures and was started on levetiracetam therapy. The following day, the dog was moderately obtunded and stumbling. On neurological examination, mild generalized ataxia was noted along with decreased menace OS, and delayed proprioception in the left pelvic and left thoracic limbs. CBC and chemistry values were unremarkable except for a mild hepatic enzyme elevation. EEG showed seizure-like activity and abnormal brain waves resembling sleep state while awake. MRI revealed an eccentric right-sided mass extending over the frontal and parietal lobes with subtentorial herniation. Due to poor prognosis, euthanasia was elected.